The 3-min Test Does not Provide a Valid Measure of Critical Power Using the SRM Isokinetic Mode - Karsten, B.; Jobson, S. A.; Hopker, J.; Passfield, L.; Beedie, C. (International Journal of Sports Medicine, 2014)
Recent datas suggest that the mean power over the final 30 s of a 3-min all-out test is equivalent to Critical Power (CP) using the linear ergometer mode. The purpose of the present study was to identify whether this is also true using an “isokinetic mode”. 13 cyclists performed: 1) a ramp test; 2) three 3-min all-out trials to establish End Power (EP) and work done above EP (WEP); and 3) 3 constant work rate trials to determine CP and the work done above CP (W′) using the work-time (=CP1/W′1) and 1/time (=CP2/W′2) models. Coefficient of variation in EP was 4.45% between trials 1 and 2, and 4.29% between trials 2 and 3. Limits of Agreement for trials 1–2 and trials 2–3 were −2±38 W. Significant differences were observed between EP and CP1 (+37 W, P<0.001), between WEP and W′1(−6.2 kJ, P=0.001), between EP and CP2 (+31 W, P<0.001) and between WEP and W′2 (−4.2 kJ, P=0.006). Average SEE values for EP-CP1 and EP-CP2 of 7.1% and 6.6% respectively were identified. Data suggest that using an isokinetic mode 3-min all-out test, while yielding a reliable measure of EP, does not provide a valid measure of CP.
Keywords: critical intensity; exercise testing; anaerobic work capacity; reliability; validity